1999
DOI: 10.2337/diabetes.48.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Islet amyloid: a long-recognized but underappreciated pathological feature of type 2 diabetes.

Abstract: Islet amyloid has been recognized as a pathological entity in type 2 diabetes since the turn of the century. It has as its unique component the islet beta-cell peptide islet amyloid polypeptide (IAPP), or amylin, which is cosecreted with insulin. In addition to this unique component, islet amyloid contains other proteins, such as apolipoprotein E and the heparan sulfate proteoglycan perlecan, which are typically observed in other forms of generalized and localized amyloid. Islet amyloid is observed at patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
398
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 455 publications
(411 citation statements)
references
References 0 publications
9
398
0
2
Order By: Relevance
“…Obese insulin-resistant subjects have slightly increased circulating IAPP and insulin [37] and TM expressing hIAPP have plasma concentrations of IAPP of 37 to 333 pmol/l compared with 10±103 pmol/l in non-transgenic mice [6,7,8,22,38,39]. Factors additional to IAPP concentrations are, however, required for amyloid formation in vivo in TM; an obese genetic back-ground or treatment to increase insulin resistance or both appears to be a prerequisite for fibril formation [40]. Recent studies in diabetic cats have shown more extensive islet amyloid in animals treated with sulphonyureas compared with those in which islet secretion was reduced by insulin therapy, providing further support for a role for increased beta-cell stimulation in islet amyloid formation [41].…”
Section: Discussionmentioning
confidence: 99%
“…Obese insulin-resistant subjects have slightly increased circulating IAPP and insulin [37] and TM expressing hIAPP have plasma concentrations of IAPP of 37 to 333 pmol/l compared with 10±103 pmol/l in non-transgenic mice [6,7,8,22,38,39]. Factors additional to IAPP concentrations are, however, required for amyloid formation in vivo in TM; an obese genetic back-ground or treatment to increase insulin resistance or both appears to be a prerequisite for fibril formation [40]. Recent studies in diabetic cats have shown more extensive islet amyloid in animals treated with sulphonyureas compared with those in which islet secretion was reduced by insulin therapy, providing further support for a role for increased beta-cell stimulation in islet amyloid formation [41].…”
Section: Discussionmentioning
confidence: 99%
“…30,32,33 IAPP aggregates to form islet amyloid in type-2 diabetes; a process which is widely believed to contribute to b-cell death in the disease. 23,28,29,32,[34][35][36][37][38][39][40] Recent studies also highlight a potentially important role for IAPP amyloid formation in the failure of islet cell grafts. [41][42][43] There is widespread interest in developing inhibitors of amyloid formation and compounds which can disaggregate preformed amyloid.…”
Section: Introductionmentioning
confidence: 99%
“…to be toxic to cultured β-cells (4), and has been proposed to play a significant role in the pathogenesis of type 2 diabetes by contributing to the destruction of β-cells in the later stages of the disease (5)(6)(7). Studies with transgenic mice that express human amylin suggest that amyloid could develop uniformly throughout the islets of the pancreas from an early stage of the disease (8).…”
mentioning
confidence: 99%